Microstructure, Mechanical Properties and Fatigue Behavior of AlSi10Mg: an Additive Manufacturing Material - Muhamad Aqil, Azri; Mohd Shamil, Shaari; Ahmad Kamal Ariffin, Mohd Ihsan; Shahrum, Abdullah (Science Publishing Corporation, 2018)
The additive manufacturing using direct metal laser sintering (DMLS) is currently gaining interest among researchers. This is due to its potential to improve the manufacturing process in the aerospace and automotive industries. This paper aims to analyse the mechanical properties, microstructure and fatigue behaviour for both conditions, as-built and heat-treated (T6). The microstructure of the as-built specimen shows ultra-fine grain boundaries whereas the heat-treated specimen showing homogenous and coarsened microstructure. The ultimate tensile strength for the as-built specimen is 392 MPa whilst the heat-treated (T6) specimen is recorded at 287 MPa. The heat-treated specimen exhibiting a significant improvement in fatigue life in all range of stresses compared to as-built during fatigue testing. Hence, the heat-treatment does improve the material characteristics as well as the fatigue behaviour. Nonetheless, more researches are needed to enhance the integrity of the AlSi10Mg produced by additive manufacturing.